Resilience and adaptation of womenpreneurs in the new normal era - Rahmi, Vembri Aulia; Hapsari, Ifahda Pratama (Community Empowerment, 2021)
The Covid-19 pandemic brings new challenges as well as new threats to the sustainability of the business of women entrepreneurs (womenpreneurs). Health protocols affect the business processes, sales and income of womenpreneurs. Meanwhile, womenpreneur skills are limited and require additional business skills to support resilience and adaptation in the new normal era. The purpose of this community service is to contribute to womenpreneurs by sharing knowledge and experiences. Participatory assistance to partners by involving the role of academies, practitioners, womenpreneurs from students and SMEs was a form of service method. The socialization and education materials delivered were about new normal business innovation behavior and product legality. The final result of the service shows that partners get business inspiration along with new knowledge and experience to support their business progress. The activity of sharing knowledge in community service implicitly implies the importance of the synergy of business actors, practitioners and womenpreneurs, both from SMEs and students to support business sustainability.